2012
DOI: 10.1371/journal.pone.0045257
|View full text |Cite
|
Sign up to set email alerts
|

Perlecan Domain V Induces VEGf Secretion in Brain Endothelial Cells through Integrin α5β1 and ERK-Dependent Signaling Pathways

Abstract: Perlecan Domain V (DV) promotes brain angiogenesis by inducing VEGF release from brain endothelial cells (BECs) following stroke. In this study, we define the specific mechanism of DV interaction with the α5β1 integrin, identify the downstream signal transduction pathway, and further investigate the functional significance of resultant VEGF release. Interestingly, we found that the LG3 portion of DV, which has been suggested to possess most of DV’s angio-modulatory activity outside of the brain, binds poorly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 49 publications
1
58
1
Order By: Relevance
“…No changes in perlecan DV were revealed suggesting that despite an increase in total perlecan staining, there is no concomitant increase in perlecan proteolysis to generate perlecan-cleaved DV. As DV is proangiogenic in the brain, 14,16 this lack of a change in DV levels is consistent with the lack of increased angiogenesis that we also observed 2 and 6 months after jTBI (discussed further below). Unchanged DV levels in the presence of increased total perlecan staining after jTBI also suggest that the activity of DV-generating proteases are unaltered or perhaps diminished.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…No changes in perlecan DV were revealed suggesting that despite an increase in total perlecan staining, there is no concomitant increase in perlecan proteolysis to generate perlecan-cleaved DV. As DV is proangiogenic in the brain, 14,16 this lack of a change in DV levels is consistent with the lack of increased angiogenesis that we also observed 2 and 6 months after jTBI (discussed further below). Unchanged DV levels in the presence of increased total perlecan staining after jTBI also suggest that the activity of DV-generating proteases are unaltered or perhaps diminished.…”
Section: Discussionsupporting
confidence: 87%
“…They are not merely components of an inert mat supporting brain cells, and growing evidence suggests that those proteins and their proteolytic fragments can be neuroprotective and affect angiogenesis. [14][15][16]18,19 As described previously, the vasoactive DV fragment of perlecan can induce neuroprotection and angiogenesis by increasing the production and release of VEGF by endothelial cells in different rodent stroke models. 14,16 It can compete with Ab for the binding to a2 integrin and thus inhibit neurotoxic pathways, 17 and it can reduce glial scar by inhibiting astrocyte proliferation.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The dissection of signaling pathways involved in this process revealed that the ERK-mediated pathway was required for GM-CSF-elicited VEGF expression. Indeed, ERK signaling is one of the major pathways that is responsible for VEGF expression induced by various stimuli in transformed or nontransformed cells (29,30). Of note, activation of ERK signaling seems to increase translocation of hypoxia-inducible factor 1a (HIF-1a) from cytoplasm to nuclei, consequently it binds to the VEGF promoter and initiates the transcription of the growth factor (31).…”
Section: Discussionmentioning
confidence: 99%
“…Kjaergaard et al [17] suggested that another heparan sulfate proteoglycan, perlecan, might be a possible ligand for YKL-40. It was revealed that perlecan comprised distinct efects on angiogenesis dependent on integrin coupling [17,18].…”
Section: Ykl-40 Ligandsmentioning
confidence: 99%